Study guides

☆☆☆

Q: What is negative 11y plus 23y?

Write your answer...

Submit

Still have questions?

Related questions

11y(2y3 - 3y + 1)

11y + 16 + 5y = 16y + 16 = 16(y + 1)

(5 - 11y - 12) + 8y = 5 - 11y - 12 + 8y = ( - 7 - 3y )

-2x -11y - 13

6y+5 = 11y+30 -25 = 5y -5 = y

5x2+56xy+11y2 = (5x+y)(x+11y) when factored

The expression is equivalent to 23y - 3.

As written, that's 17y + 4 which is in its simplest form. -6y^2 + 23y + 4 factors to (4 - y)(1 + 6y)

(y - 5)(y - 6)

6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y)

6y2 + 11y - 2 = (6y - 1) (y + 2)

Y=10

People also asked